Perlakuan Bahan Baku Rotan dengan Ekstrak Daun Mimba untuk Produk Furniture - Suheryanto, Dwi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Rattan (Calamus) have sap content (starch) are highly susceptible to insect powder as a food source. Neem leaf extract (Azadirachta indica A. Juss) contain bioactive elements that can be used as a preservative or natural pesticides. Improving the quality of raw rattan is the purpose of this study. Examples of such test manau rattan rod with a length of 20 cm and Ø ± 3-4 cm, then make the extract solution preservatives, chopped dried neem leaves boiled water in an initial temperature of 90ºC, then allowed to cool for 48 hours. Ratio of dried neem leaf extract with water extractors 1: 3; and 1: 4. Furthermore, the test sample is boiled in a solution of the extract with a variation of 1, 2, 3, and 4 hours, then observed retention and degree of damage on a regular basis every three months. The results showed that the use of neem leaf extract solution as a preservative in manau rattan significant effect on the retention and degree of damage. The higher the concentration of preservatives and treatment time, increased retention and decrease the degree of damage. Neem leaf extract with a ratio of 1: 3, the boiling time 3 hours, resulting in retention of 0.0544 g / cm3 and the degree of damage to the bottom at 0.317%.